Antibody Response to Omicron BA.4–BA.5 Bivalent Booster - Wang, Qian; Bowen, Anthony; Valdez, Riccardo; Gherasim, Carmen; Gordon, Aubree; Liu, Lihong; Ho, David D. (The New England journal of medicine, 2023)
Boosting Vaccination with BA.4–BA.5 SequencesIn a small study, a bivalent mRNA vaccine targeting omicron BA.4–BA.5 sublineages resulted in similar neutralization of other SARS-CoV-2 variants as a fourth dose of a monovalent mRNA vaccine.